Kontribusi Usaha Tani Padi dalam Meningkatkan Kesejahteraan Petani Desa Malulu Kecamatan Dondo Kabupaten Tolitoli - Arfandi, Masri; Bustari, Bustari; Adifiransyah , Moh Akram (Indo Publishing, 2026)
This study aims to determine the contribution of rice farming in improving the welfare of farmers in Malulu Village, Dondo Subdistrict, Tolitoli Regency. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The primary informants consisted of five farmers, five members of farmers’ families, and one village head as a supporting informant. The results showed that rice farming makes a tangible contribution to improving farmers’ welfare, both economically and socially. Farmers’ net income per planting season ranged from IDR 11.9 million to IDR 76 million. Rice farming also supports the fulfillment of basic needs such as family consumption, children’s education, home improvement, and savings. In addition, farmers’ participation in farmer groups provides access to production facilities assistance, although technical training remains limited.